Pengenalan Digital Marketing Bagi Pelaku Usaha UMKM Diwilayah Kabupaten Kotabaru - Periyadi Periyadi; Junaidi Junaidi; Noorlaily Maulida; Abdul Kadir. Ms; Dewi Ariefahnoor; M. Haris Syafitri; Edy Mahfudz; Sri Bulkia (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The change in marketing behavior from conventional to digital is not balanced by the existence of MSMEs who use digital marketing, even though MSMEs are believed to be able to spur the Indonesian economy. The use of digital technology-based marketing concepts is a hope for MSMEs to develop into centers of economic power. Digital marketing promotional media is expected to be an effective choice for MSMEs in developing their business and reaching national and international markets. Conventional promotional media that require a lot of money and are much more complicated are no longer the main concern for MSMEs because of digital marketing.